Manejemen Perkebunan Buah Tradisional Sebagai Sumber Penghasilan Masyarakat Lokal di Desa Nagari Sumpur Kecamatan Batipuh Selatan Kabupaten Tanah Datar Sumatera Barat - Mita Nalsalisa Br Barus; Arma Fauziah; Sri Andini; Elfayetti Elfayetti (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to examine the management of traditional fruit plantations, particularly sapodilla (sawo), as a primary source of income for the local community in Nagari Sumpur Village, Batipuh Selatan District, Tanah Datar Regency, West Sumatra. Nagari Sumpur is known as one of the largest sapodilla production centers in the province, contributing approximately 30% to the total sapodilla output of West Sumatra. Plantation management is carried out traditionally yet effectively, through a fair profit-sharing system and a quality-based marketing strategy that reflects local wisdom. This research employs a descriptive qualitative method with data collection techniques including documentation studies, literature reviews, and in-depth interviews with residents and plantation managers. The findings reveal that the sapodilla plantation management model in Nagari Sumpur plays a vital role in local economic resilience and serves as a potential example of empowerment practices based on local resources. Based on observations and analysis, it can be concluded that sapodilla plantation management in Nagari Sumpur is conducted traditionally yet effectively, with an equitable profit-sharing system, structured market segmentation based on product quality, and optimal use of the village’s geographical potential. These plantations not only serve as the main source of livelihood but also contribute significantly to both local and regional economies.